Hantavirus infection in type I interferon receptor-deficient (A129) mice. (15th October 2020) - Dowall, Stuart D.; Graham, Victoria A.; Aram, Marilyn; Findlay-Wilson, Stephen; Salguero, Francisco J.; Emery, Kirsty; Hewson, Roger
Abstract : Type I interferon receptor knockout mice (strain A129) were assessed as a disease model of hantavirus infection. A range of infection routes (intramuscular, intraperitoneal and intranasal) were assessed using minimally passaged Seoul virus (strain Humber). Dissemination of virus to the spleen, kidney and lung was observed at 5 days after intramuscular and intraperitoneal challenge, which was resolved by day 14. In contrast, intranasal challenge of A129 mice demonstrated virus tropism to the lung, which was maintained to day 14 post-challenge. These data support the use of the A129 mouse model for future infection studies and the in vivo evaluation of interventions.